Microbial contamination and metabolite exposure assessment during waste and recyclable material collection - Salambanga, Fabiola R. D. (2022)
Waste workers are exposed to bioaerosols when handling, lifting, and dumping the garbage. Bioaerosol exposure has been linked to health problems such as asthma, airway irritant symptoms, infectious, gastrointestinal, and skin diseases, and cancer. Our objective was to characterize the exposure of urban collectors and drivers to inhalable bioaerosols and to measure the cytotoxic effect of air samples in order to evaluate their health risk. Personal and ambient air sampling was conducted during the summer of 2019. Workers from 12 waste trucks collecting recyclables, organic waste, or compost were evaluated. Bacteria and fungi were cultured, molecular biology methods were used to detect microbial indicators, cytotoxic assays were performed and endotoxins and mycotoxins were quantified. Domestic waste collectors were exposed to concentrations of bacteria and endotoxins above the recommended limits, and Aspergillus section Fumigati was detected at critical concentrations in their breathing zones. Cytotoxic effects were observed in many samples, demonstrating the potential health risk for these workers. This study establishes evidence that waste workers are exposed to microbial health risks during collection. It also demonstrates the relevance of cytotoxic assays in documenting the general toxic risk found in air samples. Our results also suggest that exposures differ depending on the type of waste, job title, and discharge/unloading locations.